Preparation method of crack-free multi-element positive electrode material precursor

In the production process of ternary material precursors, the (003) crystal surfaces appear on the large particles, which solves the problem that high-nickel ternary material precursors are prone to cracks and improves the performance of materials and batteries.

CN119660832APending Publication Date: 2025-03-21GUKE ASIA PACIFIC NEW ENERGY TECHNOLOGY (SHENZHEN) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411846342.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Highly nickelized ternary material precursors are prone to crack problems during the production process, resulting in damage to performance and affecting battery performance.

Method used

By adopting special processes in the later stage of production, the (003) crystal planes appear on the surface of large particles, reducing the stress problems in too many (010) crystal planes, thereby reducing the occurrence of cracks.

Benefits of technology

It effectively reduces the crack problem of the precursor of the ternary material, improves the performance of the material and the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660832A_ABST
    Figure CN119660832A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a crack-free multi-element positive electrode material precursor. The preparation method comprises the following steps: step S1, a seed crystal preparation stage; and S2, a growth stage. At present, the (010) crystal face of a conventional ternary material precursor is basically outward, and one of the problems existing in large particles in the later growth period is a crack problem. A special process is adopted in the later stage of production, the (003) crystal face appears on the surface of a large particle, the crack problem caused by the stress problem existing in excessive (010) crystal faces is reduced, the appearing (003) crystal face occupies crack points, and therefore cracks are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nickel-based multi-element positive electrode material modification, and in particular to a method for preparing a crack-free multi-element positive electrode material precursor. Background Art

[0002] With the rapid development of the global new energy vehicle and energy storage markets, the demand for high-performance batteries continues to increase, and the market demand for ternary material precursors is also growing rapidly. The trend of high nickelization has made precursors such as NCM811 and NCA the focus of the industry because they have higher energy density and can significantly improve battery performance. In the future, with the advancement of technology and the continued growth of market demand, the ternary material precursor industry will continue to develop in the direction of high nickelization, low cost and high performance. The technological progress and capacity increase of ternary material precursors will provide a solid material foundation for the rapid development of new energy vehicles and energy storage industries. However, high-nickel ternary material precursors are prone to various problems during the production process. The biggest problem is that the spherical particles of large-particle ternary material precursors are extremely prone to cracks, which leads to damage to the performance of the ternary material precursors and even affects the performance of the corresponding ternary materials. At present, conventional ternary material precursors are basically (010) crystal planes facing outward, and one of the problems with large particles in the later stage of growth is the crack problem. Summary of the invention

[0003] The object of the present invention is to provide a method for preparing a crack-free multi-element positive electrode material precursor to solve the problems raised in the above-mentioned background technology.

[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing a crack-free multi-element positive electrode material precursor, comprising the following steps:

[0005] Step S1, seed crystal preparation stage: under an inert gas atmosphere, polybasic nickel-based sulfate solution, NaOH solution, and nitrogen-containing complexing agent are respectively added to a reactor A containing nitrogen-containing complexing agent as bottom water, the pH value in the reactor A is controlled to be 12.0-13.5, and the concentration of the nitrogen-containing complexing agent in the reactor A is controlled to be 1.0-2.0 mol / L, the stirring line speed is 5-15 m / s, and the reaction is carried out at 30-80° C. for 0.1-5.0 hours to obtain hydroxide seed crystals, D 50 1-2μm;

[0006] Step S2, growth stage: under an inert gas atmosphere, the seed crystal obtained in step S1 is placed in another reactor, and NaOH solution, nitrogen-containing complexing agent, and pure water are added to make the pH in reactor B 10.0-12.0, the concentration of nitrogen-containing complexing agent 0.1-0.5 mol / L, the seed crystal solid content 5%-10%, the stirring line speed 2-10 m / s, and the temperature 30-80°C. Then, poly-nickel-based sulfate solution, NaOH solution, and nitrogen-containing complexing agent are added to the above reactor respectively, and the reaction is started until slurry D 50 After that, the concentration of nitrogen-containing complexing agent is slowly increased to 0.5-1 mol / L, and the pH is slowly increased to 12.0-12.5 until the slurry D 50 After that, the concentration of nitrogen-containing complexing agent is gradually increased to 1-2 mol / L, and the pH is gradually increased to 12.5-13.0 until the slurry D 50 After that, the concentration of nitrogen-containing complexing agent is gradually reduced to 0.1-0.3 mol / L, and the pH is gradually reduced to 10.0-11.0 until the slurry D 50 Reach 9-13μm; wash and dry the slurry to obtain a crack-free multi-material precursor.

[0007] Preferably, the nitrogen-containing complexing agent is one or a combination of ammonia water, ammonium sulfite, ammonium bisulfite, ammonium bisulfate, ammonium sulfide, ammonium hydrogensulfide, ammonium thiosulfate or ammonium carbonate.

[0008] Preferably, the polynary nickel-based sulfate is XSO4, wherein X must include Ni, and the other elements are one or more of Co, Mn, Al, Mg, Ti, and Sr.

[0009] Preferably, the molar concentration of the nickel-based sulfate solution in step S1 is 1.0-3.0 mol / L, the molar concentration of the NaOH solution is 2.0-7.0 mol / L, the molar concentration of the nitrogen-containing complexing agent is 5.0-15.0 mol / L, and the concentration of the nitrogen-containing complexing agent in the reactor A is controlled to be 0.3-0.5 mol / L.

[0010] Preferably, the molar concentration of the polybasic nickel-based sulfate solution in step S2 is 1.0-3.0 mol / L, the molar concentration of the NaOH solution is 2.0-7.0 mol / L, the molar concentration of the nitrogen-containing complexing agent is 5.0-15.0 mol / L, and the concentration of the nitrogen-containing complexing agent in reactor B is controlled to be 0.3-0.5 mol / L.

[0011] Preferably, the multi-material precursor obtained in step S2 is uniformly mixed with a lithium-containing compound and calcined to obtain a crack-free multi-material positive electrode material, wherein the lithium-containing compound is one or a combination of lithium hydroxide, lithium carbonate, lithium acetate or lithium nitrate.

[0012] Compared with the prior art, the present invention has the following beneficial effects:

[0013] At present, the conventional ternary material precursors are basically (010) crystal planes facing outwards, and one of the problems with large particles in the later stages of growth is cracking. This patent uses a special process in the later stages of production to allow (003) crystal planes to appear on the surface of large particles, reducing the cracking problem caused by stress problems with too many (010) crystal planes. The (003) crystal planes that appear will occupy the crack points, thereby reducing the occurrence of cracks.

[0014] The above description is only an overview of the technical solution of the embodiment of the present application. In order to more clearly understand the technical means of the embodiment of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the embodiment of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present application, a brief introduction will be given below to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0016] Figure 1 This is a SEM image of the multi-element positive electrode material precursor prepared in the present invention.

[0017] Figure 2 This is the SEM image of the precursor of the multi-electrode material in the comparative example.

[0018] Figure 3 This is the SEM image of the conventional ternary material precursor. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in the specification of the application are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification, claims and drawings of this application are intended to cover non-exclusive inclusions.

[0021] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0022] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.

[0023] Example 1

[0024] 1) Step S1, seed preparation stage: under nitrogen atmosphere, 1.5 mol / L XSO4 (M = Ni, Co, Mn, wherein the molar ratio of Ni: Co: Mn is 0.90: 0.05: 0.05) mixed solution, 6.0 mol / L NaOH solution, 10.0 mol / L ammonia solution were added to reactor A containing 0.4 mol / L ammonia solution as bottom water at different feeding rates (the feeding rates of XSO4 solution, first liquid alkali solution, and first nitrogen-containing complexing agent were 15 L / h, 8 L / h, and 0.6 L / h, respectively), the pH value of the coprecipitation reaction was controlled to be 12.8, the temperature of the coprecipitation reaction was controlled to be 55°C, the ammonia concentration in the coprecipitation reactor A was controlled to be 1.4 mol / L, the feeding was continued, and the reaction was carried out for 1 hour to obtain Ni 0.90 Co 0.05 Mn 0.05 (OH)2 seeds, particle size D50 is about 1 μm;

[0025] 2) Step S2, growth stage: under nitrogen atmosphere, the seed crystal obtained in step S1 is put into another reactor B, and NaOH solution, nitrogen-containing complexing agent and pure water are added to make the pH in reactor B be 11, the concentration of nitrogen-containing complexing agent be 0.2 mol / L, the solid content of seed crystal be 10%, the stirring line speed be 8 m / s, and the temperature be 55°C. Then, 1.5 mol / L XSO4 solution, 6.0 mol / L NaOH solution and 10.0 mol / L ammonia solution are added to the above reactor respectively, and the reaction is carried out for 30 hours until the slurry D50 reaches 5 μm; then the concentration of nitrogen-containing complexing agent is adjusted to be slowly increased to 0.7 mol / L, and the pH is slowly increased to 12.0, until the slurry D50 reaches 7 μm; then the concentration of nitrogen-containing complexing agent is adjusted to be gradually increased to 1.5 mol / L, and the pH is gradually increased to 12.8, until the slurry D 50 The slurry was washed and dried to obtain a Ni-free slurry. 0.90 Co 0.05 Mn 0.05 (OH)2 precursor.

[0026] 3) Using Ni from step 2) 0.90 Co 0.05 Mn 0.05 The (OH)2 precursor was mixed with LiOH·H2O and then placed in a tube furnace. The temperature was raised to 500°C at a heating rate of 5°C / min and then kept at this temperature for 6 hours. The temperature was then raised to 780°C at a heating rate of 3°C / min and then kept at this temperature for 13 hours to obtain LiNi 0.90 Co 0.05 Mn 0.05 O2 positive electrode material.

[0027] 4) Using the LiNi prepared above 0.90 Co 0.05 Mn 0.05 After the O2 positive electrode material was washed and coated, the electrode was prepared and assembled into a CR2032 button battery. The electrochemical performance was tested as follows: Figure 1 It can be seen that its first coulombic efficiency is 92%, the 0.1C cycle capacity is as high as 220mAh / g, and after 100 cycles at 0.1C, the capacity retention rate is as high as 97%.

[0028] Example 2

[0029] 1) Step S1, seed preparation stage: under nitrogen atmosphere, 2.0 mol / L XSO4 (M = Ni, Co, Mn, Al, wherein the molar ratio of Ni: Co: Mn: Al is 0.94: 0.03: 0.02: 0.01) mixed solution, 10.0 mol / L NaOH solution, 10.0 mol / L ammonia solution were added to reactor A containing 0.5 mol / L ammonia solution as bottom water at different feeding rates (the feeding rates of XSO4 solution, first liquid alkali solution, and first nitrogen-containing complexing agent were 15 L / h, 8 L / h, and 0.6 L / h, respectively), the pH value of the coprecipitation reaction was controlled to be 12.5, the temperature of the coprecipitation reaction was controlled to be 55°C, the concentration of ammonia solution in the coprecipitation reactor A was controlled to be 1.4 mol / L, the feeding was continued, and the reaction was carried out for 1 hour to obtain Ni 0.94 Co 0.03 Mn 0.02 Al 0.01 (OH)2 seeds, particle size D50 is about 1 μm;

[0030] 2) Step S2, growth stage: under nitrogen atmosphere, the seed crystal obtained in step S1 is put into another reactor B, and NaOH solution, nitrogen-containing complexing agent and pure water are added to make the pH in reactor B 11.5, the concentration of nitrogen-containing complexing agent is 0.3 mol / L, the solid content of seed crystal is 8%, the stirring line speed is 10 m / s, and the temperature is 55°C. Then, 2.0 mol / L XSO4 solution, 10.0 mol / L NaOH solution and 10.0 mol / L ammonia solution are added to the above reactor respectively, and the reaction is carried out for 30 hours until slurry D is obtained. 50 Then the concentration of ammonia solution was adjusted to 0.5 mol / L and the pH was slowly increased to 12.2 until the slurry D50 reached 7 μm; then the concentration of nitrogen-containing complexing agent was adjusted to 1.5 mol / L and the pH was gradually increased to 12.7 until the slurry D 50 After that, the concentration of ammonia solution was gradually reduced to 0.3 mol / L, and the pH was gradually reduced to 11.0 until the slurry D 50 Reach 12μm; wash and dry the slurry to obtain crack-free Ni 0.94 Co 0.03 Mn 0.02 Al 0.01 (OH)2 precursor.

[0031] 3) Using Ni from step 2) 0.94 Co 0.03 Mn 0.02 Al 0.01The (OH)2 precursor was mixed with LiOH·H2O and then placed in a tube furnace. The temperature was raised to 500°C at a heating rate of 5°C / min and then kept at this temperature for 6 hours. The temperature was then raised to 730°C at a heating rate of 3°C / min and then kept at this temperature for 13 hours to obtain LiNi 0.94 Co 0.03 Mn 0.02 Al 0.01 O2 positive electrode material.

[0032] 4) Using the LiNi prepared above 0.94 Co 0.03 Mn 0.02 Al 0.01 After the O2 positive electrode material was washed and coated, the electrode was prepared and assembled into a CR2032 button battery. The electrochemical performance was tested as follows: Figure 1 It can be seen that its first coulombic efficiency is 93%, the 0.1C cycle capacity is as high as 230mAh / g, and after 100 cycles at 0.1C, the capacity retention rate is as high as 98%.

[0033] Comparative Example 1

[0034] 1) Step S1, seed preparation stage: under nitrogen atmosphere, 1.5 mol / L XSO4 (M = Ni, Co, Mn, wherein the molar ratio of Ni: Co: Mn is 0.90: 0.05: 0.05) mixed solution, 6.0 mol / L NaOH solution, 10.0 mol / L ammonia solution were added to reactor A containing 0.4 mol / L ammonia solution as bottom water at different feeding rates (the feeding rates of MSO4 solution, first liquid alkali solution, and first nitrogen-containing complexing agent were 15 L / h, 8 L / h, and 0.6 L / h, respectively), the pH value of the coprecipitation reaction was controlled to be 12.8, the temperature of the coprecipitation reaction was controlled to be 55°C, the ammonia concentration in the coprecipitation reactor A was controlled to be 1.4 mol / L, the feeding was continued, and the reaction was carried out for 1 hour to obtain Ni 0.90 Co 0.05 Mn 0.05 (OH)2 seed, particle size D 50 About 1 μm;

[0035] 2) Step S2, growth stage: under nitrogen atmosphere, the seed crystal obtained in step S1 was put into another reactor B, and NaOH solution, nitrogen-containing complexing agent and pure water were added to make the pH in reactor B 11, the concentration of nitrogen-containing complexing agent 0.2 mol / L, the seed crystal solid content 10%, the stirring line speed 8 m / s, and the temperature 55°C. Then, 1.5 mol / L XSO4 solution, 6.0 mol / L NaOH solution and 10.0 mol / L ammonia solution were added to the above reactor respectively, and the reaction was carried out for 50 hours. 50Reach 12μm; wash and dry the slurry to obtain Ni 0.90 Co 0.05 Mn 0.05 (OH)2 precursor.

[0036] 3) Using Ni from step 2) 0.90 Co 0.05 Mn 0.05 The (OH)2 precursor was mixed with LiOH·H2O and then placed in a tube furnace. The temperature was raised to 500°C at a heating rate of 5°C / min and then kept at this temperature for 6 hours. The temperature was then raised to 780°C at a heating rate of 3°C / min and then kept at this temperature for 13 hours to obtain LiNi 0.90 Co 0.05 Mn 0.05 O2 positive electrode material.

[0037] 4) Using the LiNi prepared above 0.90 Co 0.05 Mn 0.05 After the O2 positive electrode material was washed and coated, the electrode was prepared and assembled into a CR2032 button cell. The electrochemical performance was tested as follows: Figure 2 As shown, its first coulombic efficiency is only 88%, the 0.1C cycle capacity is only 210mAh / g, and after 100 cycles at 0.1C, the capacity retention rate is only 83%.

[0038] like Figure 3 As shown, currently, the conventional ternary material precursors are basically (010) crystal planes facing outwards, and one of the problems with large particles in the later stages of growth is cracking. This patent uses a special process in the later stages of production to allow (003) crystal planes to appear on the surface of large particles, reducing the cracking problem caused by the stress problem of too many (010) crystal planes. The (003) crystal planes that appear will occupy the crack points, thereby reducing the occurrence of cracks.

[0039] As described above, the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a crack-free multi-element cathode material precursor, characterized in that: The following steps are involved: Step S1, seed crystal preparation stage: under an inert gas atmosphere, polybasic nickel-based sulfate solution, NaOH solution, and nitrogen-containing complexing agent are respectively added to a reactor A containing nitrogen-containing complexing agent as bottom water, the pH value in the reactor A is controlled to be 12.0-13.5, and the concentration of the nitrogen-containing complexing agent in the reactor A is controlled to be 1.0-2.0 mol / L, the stirring line speed is 5-15 m / s, and the reaction is carried out at 30-80° C. for 0.1-5.0 hours to obtain hydroxide seed crystals, D 50 1-2μm; Step S2, growth stage: under an inert gas atmosphere, the seed crystal obtained in step S1 is put into another reactor, and NaOH solution, nitrogen-containing complexing agent and pure water are added to make the pH in reactor B be 10.0-12.0, the concentration of nitrogen-containing complexing agent be 0.1-0.5 mol / L, the solid content of seed crystal be 5%-10%, the stirring line speed be 2-10 m / s, the temperature be 30-80°C, then polybasic nickel-based sulfate solution, NaOH solution and nitrogen-containing complexing agent be added into the above reactor respectively, and the reaction is started until slurry D 50 After that, the concentration of nitrogen-containing complexing agent is slowly increased to 0.5-1 mol / L, and the pH is slowly increased to 12.0-12.5 until the slurry D 50 Then the concentration of nitrogen-containing complexing agent is gradually increased to 1-2 mol / L, and the pH is gradually increased to 12.5-13.0, until the slurry D50 reaches 7-9 μm; then the concentration of nitrogen-containing complexing agent is gradually reduced to 0.1-0.3 mol / L, and the pH is gradually reduced to 10.0-11.0, until the slurry D 50 Reach 9-13μm; wash and dry the slurry to obtain a crack-free multi-material precursor.

2. The method for preparing a crack-free multi-element positive electrode material precursor according to claim 1, characterized in that: The nitrogen-containing complexing agent is one or a combination of ammonia water, ammonium sulfite, ammonium bisulfite, ammonium bisulfate, ammonium sulfide, ammonium hydrogensulfide, ammonium thiosulfate or ammonium carbonate.

3. The method for preparing a crack-free multi-element positive electrode material precursor according to claim 1, characterized in that: The polynary nickel-based sulfate is XSO4, wherein X must include Ni, and the other elements are one or more of Co, Mn, Al, Mg, Ti, and Sr.

4. The method for preparing a crack-free multi-element positive electrode material precursor according to claim 1, characterized in that: The molar concentration of the nickel-based sulfate solution in step S1 is 1.0-3.0 mol / L, the molar concentration of the NaOH solution is 2.0-7.0 mol / L, the molar concentration of the nitrogen-containing complexing agent is 5.0-15.0 mol / L, and the concentration of the nitrogen-containing complexing agent in the reactor A is controlled to be 0.3-0.5 mol / L.

5. The method for preparing a crack-free multi-element positive electrode material precursor according to claim 1, characterized in that: The molar concentration of the polybasic nickel-based sulfate solution in step S2 is 1.0-3.0 mol / L, the molar concentration of the NaOH solution is 2.0-7.0 mol / L, the molar concentration of the nitrogen-containing complexing agent is 5.0-15.0 mol / L, and the concentration of the nitrogen-containing complexing agent in the reactor B is controlled to be 0.3-0.5 mol / L.

6. The method for preparing a crack-free multi-element positive electrode material precursor according to claim 1, characterized in that: The multi-material precursor obtained in step S2 is uniformly mixed with a lithium-containing compound and calcined to obtain a crack-free multi-material positive electrode material. The lithium-containing compound is one or a combination of lithium hydroxide, lithium carbonate, lithium acetate or lithium nitrate.

7. The method for preparing a crack-free multi-element positive electrode material precursor according to claim 6, characterized in that: The calcination treatment comprises the following specific steps: heating to 450-550°C at 2°C / min and keeping the temperature for 4-6 hours; then heating to 700-900°C at 2-5°C / min and keeping the temperature for 10-15 hours.

Citation Information

Cited By

  • Method for preparing narrow-particle-size crack-free large-particle ternary precursor by intermittently combining discharging and separating kettles

    CN122187156A